Correction to: Exploring the differences between men's and women's perceptions of gender-based violence in rural Tajikistan: a qualitative study - Elizabeth A. Wood; Karina E. Wilson; K. D. Jacobs (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article 10.1186/s12905-021-01266-9.